Saline water and bovine biofertilizer chemically enriched on jackfruit seedlings var. soft (Bioscience Journal, 2020)
Water scarcity and water quality is a subject of constant debate around the world, with the accumulation of salts in water and on soils causing a negative impact on food production, man and herds, especially in the arid and semi-arid regions. The use of bovine manure biofertilizers that potentiate the use of brackish water, normally restricted in agriculture due to its salinity, has been suggested for seedling formation and crop production, including jackfruit plants. An experiment was carried out from October/2012 to February/2013, in a protected environment, at Agrarian Sciences Center, Federal University of Paraíba, Areia county, Paraíba State, Brazil, to evaluate the effects of saline water and bovine biofertilizer chemically enriched with gypsum, cow's milk and molasses. The experimental design was completely randomized, with five replications of a plant, in a factorial scheme 5 × 2, corresponding   at values of electrical conductivity of the water of 0.5, 1.0, 2.0, 3.0 and 4.0 dS m-1 substrate with and without bovine biofertilizer. Measurements were made of substrate salinity, height of growth, stem diameter, length mean root, leaf area, leaf area ratio, and total dry mass (root, shoots and leaves). The biofertilizer enriched with cow's milk, sugar cane molasses and agricultural gypsum increased the salinity of the soil; however, it attenuated the negative effects of the salts during establishment of jackfruit seedlings, to 95 days after emergence. All the growth variables studied were higher for seedlings developed in substrate with bovine biofertilizer chemically enriched.